Electrochemical cells, electrochemical cells with separators, electrochemical cell stacks, hot modules, hydrogen production equipment

JP2026166249APending Publication Date: 2026-10-14NITERRA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025059086
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0109】 (効果の説明) 以上の説明のとおり、上記形態の空気極29,129,229,329は、主成分としてのペロブスカイト構造を有する複合酸化物と、シリコン、クロム、硫黄の少なくとも一種を含む副成分を含有し、電気化学セル20は、燃料ガスが流れる燃料ガス流方向21Dにおいて、第1領域G1と、第1領域G1よりも下流側に位置する第2領域G2とを有し、空気極29,129,229,329のうち、第1領域G1に配される第1部分81の第1体積内における副成分の含有率は、空気極29,129,229,329のうち、第2領域G2に配される第2部分82の第2体積内における副成分の含有率よりも大きい。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166249000001_ABST
    Figure 2026166249000001_ABST
Patent Text Reader

Abstract

This technology provides a way to suppress the occurrence of cracks in the air electrode. [Solution] The electrochemical cell 20 is based on general formula A1 x A2 y BO 3-δ The electrochemical cell 20 comprises an air electrode 29 mainly containing a composite oxide having a perovskite structure represented by (where 0.9 ≤ x + y < 1, δ is the amount of oxygen deficiency), a fuel electrode 21 to which a fuel gas containing water vapor is supplied, and a solid electrolyte layer 24 disposed between the air electrode 29 and the fuel electrode 21, wherein the air electrode 29 contains at least one of silicon, chromium, and sulfur as a minor component, and the electrochemical cell 20 has a first region G1 and a second region G2 located downstream of the first region G1 in the fuel gas flow direction 21D, and the content of the minor component in the first volume of the first part 81 of the air electrode 29 located in the first region G1 is greater than the content of the minor component in the second volume of the second part 82 of the air electrode 29 located in the second region G2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an electrochemical cell, an electrochemical cell with a separator, an electrochemical cell stack, a hot module, and a hydrogen production apparatus.

Background Art

[0002] A solid oxide fuel cell (hereinafter referred to as "SOFC") that generates power using an electrochemical reaction between hydrogen and oxygen is known. For example, a unit cell of a fuel cell, which is a constituent unit of the SOFC described in Patent Document 1, includes an electrolyte layer containing a solid oxide, an air electrode disposed on one side of the electrolyte layer, and a fuel electrode disposed on the other side of the electrolyte layer. Oxide ions dissociated from oxygen supplied to the air electrode move to the fuel electrode based on the oxygen conductivity of the solid electrolyte, react with hydrogen contained in the fuel gas supplied to the fuel electrode to generate water vapor, and generate electricity.

[0003] The above SOFC can be used as a solid oxide electrolysis cell (hereinafter simply referred to as "SOEC") by passing current in the reverse direction, and is known to be used as an energy storage technology in a form that converts water vapor into hydrogen using surplus power or the like, which has been a problem in the process of introducing renewable energy. When water vapor is supplied to the fuel electrode and a current is passed between the air electrode and the fuel electrode, the water vapor is electrolyzed to generate hydrogen from the fuel electrode, and oxide ions generated at the fuel electrode move to the air electrode based on the oxygen conductivity of the solid electrolyte, generating oxygen from the air electrode.

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Summary of the Invention

Problems to be Solved by the Invention

[0005] Generally, in SOFCs, oxygen is consumed at the fuel electrode during use, causing a decrease in gas pressure in the air chamber. However, in SOECs, oxygen is generated at the air electrode during use, which can increase the gas pressure in the air chamber. Additionally, the rapid increase in gas pressure due to the vaporization of water vapor (the fuel gas) can cause different stresses than in SOFCs, potentially leading to cracks in the air electrode. Furthermore, in SOECs, technologies to suppress the decrease in current density are generally desired. [Means for solving the problem]

[0006] This disclosure can be implemented in the following forms:

[0007] (1) According to one aspect of this disclosure, General formula A1 x A2 y BO 3-δ An electrochemical cell is provided, comprising: an air electrode containing a composite oxide having a perovskite structure represented by (where 0.9 ≤ x + y < 1, and δ is the amount of oxygen deficiency) as the main component; a fuel electrode to which fuel gas is supplied; and a solid electrolyte layer disposed between the air electrode and the fuel electrode, wherein the air electrode contains at least one of silicon, chromium, and sulfur as a minor component; the electrochemical cell has a first region and a second region located downstream of the first region in the fuel gas flow direction through which the fuel gas flows; and the content of the minor component in a first volume of the portion of the air electrode located in the first region is greater than the content of the minor component in a second volume of the portion of the air electrode located in the second region. With the air electrode of this form of electrochemical cell, the occurrence of cracks in the air electrode can be suppressed when the electrochemical cell is in use.

[0008] In the air electrode, it is presumed that sinterability is improved by preparing at least one of silicon, chromium, and sulfur as a minor component, as this minor component fills the gaps between particles of the main component, a composite oxide having a perovskite structure. In the fuel electrode, oxide ions are more likely to be generated in the upstream region in the direction of fuel gas flow than in the downstream region. For this reason, in the air electrode, the portion where more oxide ions reach via the solid electrolyte layer tends to have a higher oxygen generation rate compared to other parts. As a result, the gas pressure is higher in the portion of the air electrode located in the first region than in the portion located in the second region, and it is thought that cracks are more likely to occur due to the pressure difference. In the air electrode, if the content of the minor component is set to the above-mentioned content, it is thought that the bonding force between particles in the air electrode in the portion located in the first region will become stronger. As a result, the electrochemical cell according to this disclosure can suppress the occurrence of cracks and improve the durability of the air electrode.

[0009] (2) The electrochemical cell described in (1) above may be used as a solid oxide type electrolytic cell. This form of electrochemical cell can suppress the occurrence of cracks in the air electrode.

[0010] (3) In the electrochemical cell described in (1) or (2) above, the content of the minor component in the first volume may be 0.01% by mass or more and 5.0% by mass or less, and the content of the minor component in the second volume may be 0.001% by mass or more and 1.5% by mass or less. According to this form of electrochemical cell, the occurrence of cracks in the air electrode can be suppressed.

[0011] (4) In the electrochemical cell described in any of (1) to (3) above, the content of the minor component may be the content within a volume of 10% to 90% from the surface relative to the thickness of the air electrode. This form of electrochemical cell can suppress the occurrence of cracks in the air electrode.

[0012] (5) In the electrochemical cell according to any one of (1) to (4) above, the fuel gas may be supplied to the fuel electrode at a flow rate of 25 liters / (min·cm 2 ) to 130 liters / (min·cm 2 ) or less for use. According to the electrochemical cell of this embodiment, the occurrence of cracks in the air electrode can be suppressed.

[0013] (6) In the electrochemical cell according to any one of (1) to (5) above, a gas containing oxygen may be supplied to the air electrode at a flow rate of 30 liters / (min·cm 2 ) to 50 liters / (min·cm 2 ) or less for use. According to the electrochemical cell of this embodiment, the occurrence of cracks in the air electrode can be suppressed.

[0014] (7) In the electrochemical cell according to any one of (1) to (6) above, the volume of the air chamber facing the air electrode may be 9 cm 3 or more and 11 cm 3 or less. According to the electrochemical cell of this embodiment, the occurrence of cracks in the air electrode can be suppressed.

[0015] (8) In the electrochemical cell according to any one of (1) to (7) above, when the main component of the air electrode is La x Sr y CoO 3-δ or La x Sr y CoFeO 3-δ , the content ratio of the subcomponent in the second volume to the content ratio of the subcomponent in the first volume may be 0.1 or more and 0.9 or less. According to the electrochemical cell of this embodiment, the occurrence of cracks in the air electrode can be suppressed.

[0016] (9) In the electrochemical cell according to any one of (1) to (7) above, the main component of the air electrode is Sm x Sr y CoO 3-δIn this case, the ratio of the content of the minor component in the second volume to the ratio of the content of the minor component in the first volume may be 0.1 or more and 0.9 or less. According to this form of electrochemical cell, the occurrence of cracks in the air electrode can be suppressed.

[0017] (10) According to another embodiment of the present disclosure, an electrochemical cell with a separator is provided, comprising an electrochemical cell according to any one of (1) to (9) above, wherein a separator with an open center is disposed in the solid electrolyte layer. Using this form of electrochemical cell with a separator, the occurrence of cracks in the air electrode can be suppressed.

[0018] (11) According to another embodiment of the present disclosure, an electrochemical cell stack is provided, comprising a plurality of electrochemical cells stacked according to any one of (1) to (9) above. Using this form of electrochemical cell stack, the occurrence of cracks in the air electrode can be suppressed.

[0019] (12) Another embodiment of the present disclosure provides a hot module comprising: an electrochemical cell stack as described in (11) above; a vaporizer that generates water vapor supplied to the electrochemical cell stack; a heat exchanger that performs heat exchange with a gas supplied to the electrochemical cell stack; a heater for heating the electrochemical cell stack; and an insulating material that houses the electrochemical cell stack, the vaporizer, the heat exchanger, and the heater inside. Using this form of hot module, the occurrence of cracks in the air electrode can be suppressed.

[0020] (13) According to another embodiment of the present disclosure, a hydrogen production apparatus is provided which comprises the hot module described in (12) above. Using this form of hot module, the occurrence of cracks in the air electrode can be suppressed.

[0021] Furthermore, the present invention can be realized in various forms, for example, in the form of a method for manufacturing an electrochemical cell. [Brief explanation of the drawing]

[0022] [Figure 1] A perspective view showing the external configuration of an electrochemical cell stack as one embodiment of the present disclosure. [Figure 2] Figure 1 shows a schematic diagram of the disassembled electrochemical cell stack cut along line II-II. [Figure 3] Schematic diagram of the top view of an electrochemical cell with a separator. [Figure 4] Block diagram of a hydrogen production system. [Figure 5] A cross-sectional view showing the configuration of the reaction unit 11 according to the embodiment. [Figure 6] A plan view of the air electrode according to the embodiment. [Figure 7] A cross-sectional view and a plan view showing the configuration of an air electrode according to another embodiment. [Figure 8] A cross-sectional view and a plan view showing the configuration of an air electrode according to another embodiment. [Figure 9] A cross-sectional view and a plan view showing the configuration of an air electrode according to another embodiment. [Modes for carrying out the invention]

[0023] Figure 1 is a perspective view showing the external configuration of an electrochemical cell stack 10 as one embodiment of the present disclosure. The electrochemical cell stack 10 in this embodiment is a stack of solid oxide electrolysis cells (SOECs) in which the solid electrolyte layer 24, described later, is formed of solid oxide. Figure 1 shows an example of the configuration of the electrochemical cell stack 10.

[0024] The electrochemical cell stack 10 includes multiple rectangular reaction units 11 stacked in the thickness direction, and approximately rectangular end plates 12 and 13 that sandwich the reaction units 11 in the thickness direction. Bolts 14 are positioned at the four corners of the periphery of the electrochemical cell stack 10, penetrating the end plates 12, the reaction units 11, and the end plates 13 in the thickness direction. The reaction units 11 and the end plates 12 and 13 are fastened together by the bolts 14.

[0025] The electrochemical cell stack 10 includes a terminal plate 52 positioned between the end plate 12 and the reaction units 11, and a terminal plate 53 positioned between the end plate 13 and the reaction units 11. Multiple reaction units 11 are connected in series between the terminal plates 52 and 53. The protruding portions of the terminal plates 52 and 53 function as terminals. It is, of course, possible to omit the terminal plates 52 and 53 and electrically connect the reaction units 11 to the end plates 12 and 13, thereby making the end plates 12 and 13 the terminals of the electrochemical cell stack 10.

[0026] Four spaces are formed around the periphery of the electrochemical cell stack 10, penetrating in the thickness direction. These four spaces function as passages 15a for fuel gas to enter the fuel chamber 33 (described later) of the reaction unit 11 from outside the electrochemical cell stack 10, passage 15b for fuel gas to exit the fuel chamber 33 to outside the electrochemical cell stack 10, passage 15c for gas to enter the air chamber 35 (described later) of the reaction unit 11 from outside the electrochemical cell stack 10, and passage 15d for gas to exit the air chamber 35 to outside the electrochemical cell stack 10.

[0027] The direction in which the fuel gas flows through the fuel chamber 33 can be adjusted by the relative positions of passages 15a and 15b. The direction in which the fuel gas flows through the fuel chamber 33 will also be referred to below as the "fuel gas flow direction 21D". The direction in which the oxidizer gas flows through the air chamber 35 can be adjusted by the relative positions of passages 15c and 15d. The oxidizer gas usually flows through the air chamber 35 from passage 15c to passage 15d, but is not limited to this. For example, the oxidizer gas may flow through the air chamber 35 from passage 15d to passage 15c.

[0028] Figure 2 is an exploded schematic diagram of the electrochemical cell stack 10, cut along the line II-II in Figure 1, passing through passages 15a and 15b. Figure 2 shows a schematic cross-sectional view along the line II-II, with the components constituting a single reaction unit 11 separated in the thickness direction. The reaction unit 11 includes, in order in the thickness direction, an interconnector 16, a fuel electrode frame 17, an electrochemical cell with separator 47, and an air electrode frame 19. Note that the thickness of each part is exaggerated in Figure 2.

[0029] Figure 3 is a schematic top view of an electrochemical cell 47 with a separator. The electrochemical cell 47 with a separator includes an electrochemical cell 20 and a separator 30 placed in the electrochemical cell 20. Holes (passages 15a, 15b, 15c, 15d) pass through the interconnector 16, fuel electrode frame 17, separator 30, and air electrode frame 19. The electrochemical cell 20 will be described later.

[0030] The separator 30 is a roughly rectangular frame-shaped member with an opening 37 in the center that is larger than the air electrode 29, which will be described later. Stainless steel is an example of a material for the separator 30. The separator 30 is airtightly joined to the surface 24a of the solid electrolyte layer 24, which will be described later, by brazing material 31, avoiding the air electrode 29.

[0031] The interconnectors 16 are located at both ends of the electrochemical cell 20 in the thickness direction. The interconnectors 16 are formed from conductive, substantially rectangular plate-like members. The interconnectors 16 electrically connect adjacent reaction units 11 in the thickness direction. Stainless steel is an example of a material for the interconnectors 16.

[0032] The fuel electrode frame 17 is a roughly rectangular frame-shaped member positioned between the interconnector 16 and the separator 30. Stainless steel is an example of a material for the fuel electrode frame 17. The fuel electrode frame 17 surrounds the electrochemical cell 20 and the current collector FC1 located in the center of the interconnector 16.

[0033] The current collector FC1 electrically connects the fuel electrode 21 and the interconnector 16. An example of a material for the current collector FC1 is a porous metal such as Ni that is gas permeable. Inside the fuel electrode frame 17, a fuel chamber 33 is formed, surrounded by the interconnector 16, the fuel electrode frame 17, and the separator 30. A slit extending in the fuel gas flow direction 21D is formed on the surface of the current collector FC1. Therefore, when the current collector FC1 and the fuel electrode 21 are facing each other, the surface of the fuel electrode 21 has a region that contacts the current collector FC1 and a region that does not. As a result, the fuel gas flowing inside the fuel chamber 33 can flow over the surface of the fuel electrode 21.

[0034] The air electrode frame 19 is a roughly rectangular frame-shaped member positioned between the interconnector 16 and the separator 30. An example of the material for the air electrode frame 19 is an insulator such as mica. The air electrode frame 19 surrounds the current collector AC1, which is located in the center of the interconnector 16. The current collector AC1 electrically connects the air electrode 29 and the interconnector 16. In this embodiment, the current collector AC1 is formed integrally with the interconnector 16, but this is not the only option. It is certainly possible to make the current collector AC1 a separate component from the interconnector 16.

[0035] An air chamber 35 is formed inside the air electrode frame 19, surrounded by the interconnector 16, the air electrode frame 19, and the separator 30. A slit is formed on the surface of the current collector AC1, extending in the direction in which the oxidizing gas flows inside the air chamber 35. Therefore, when the current collector AC1 and the air electrode 29 are facing each other, the surface 29A of the air electrode 29 has a region that is in contact with the current collector AC1 and a region that is not in contact. As a result, the oxidizing gas flowing inside the air chamber 35 can flow over the surface 29A of the air electrode 29. The separator 30 separates the fuel chamber 33 and the air chamber 35, preventing the fuel gas in the fuel chamber 33 from mixing with the oxidizing gas (oxygen, air, etc.) in the air chamber 35.

[0036] The hydrogen production apparatus 60 and hot module 61, which include an electrochemical cell stack 10, will be described with reference to Figure 4. Figure 4 is a block diagram of the hydrogen production apparatus 60. The hydrogen production apparatus 60 is a device that produces hydrogen from water and includes a hot module 61.

[0037] The hot module 61 comprises an electrochemical cell stack 10, a vaporizer 62 that generates water vapor supplied to the electrochemical cell stack 10, a heat exchanger 63 that performs heat exchange between the gas supplied to the electrochemical cell stack 10 and the gas generated by the electrochemical cell stack 10, a heater 64 that heats the electrochemical cell stack 10, and an insulating material 65. In the hot module 61, the insulating material 65 houses the electrochemical cell stack 10, vaporizer 62, heat exchanger 63, and heater 64 inside in order to reduce heat dissipation.

[0038] The vaporizer 62 includes a heat exchanger that exchanges heat with a high-temperature gas containing oxygen produced by the electrochemical cell stack 10, and heats water to produce steam. The steam produced by the vaporizer 62 contains hydrogen, which reduces the oxidation of the catalyst contained in the fuel electrode 21. The hydrogen-containing steam exchanges heat with the hydrogen and oxygen produced by the electrochemical cell stack 10 by the heat exchanger 63, and is then heated by the heater 64 to the operating temperature of the electrochemical cell stack 10 and supplied to the fuel chamber 33 of the electrochemical cell stack 10. The air exchanges heat with the hydrogen and oxygen produced by the electrochemical cell stack 10 by the heat exchanger 63, and is then heated by the heater 64 to the operating temperature of the electrochemical cell stack 10 and supplied to the air chamber 35 of the electrochemical cell stack 10.

[0039] Examples of insulation materials 65 include ceramic wool, refractory ceramic fiber (RCF), heat-resistant fibers such as biosoluble fiber (AES), and heat-resistant containers formed from heat-resistant fibers. The heat-resistant fibers fill the gaps between the electrochemical cell stack 10, the vaporizer 62, the heat exchanger 63, and the heater 64. The condenser 66 is a device for cooling hydrogen gas, and the liquefied water is supplied to the vaporizer 62 as raw water.

[0040] (Electrochemical cell) As shown in Figure 2, the electrochemical cell 20 comprises an air electrode 29, a fuel electrode 21, and a solid electrolyte layer 24 provided between the air electrode 29 and the fuel electrode 21. As shown in Figure 5, the electrochemical cell 20 has a first region G1 and a second region G2 located downstream of the first region G1 in the fuel gas flow direction 21D. In the fuel gas flow direction 21D, the first region G1 is located upstream of the second region G2. In this embodiment, the first region G1 is the region of the electrochemical cell 20 upstream of the center line CL in the fuel gas flow direction 21D. However, the first region G1 only needs to be located upstream of the second region G2, and the shape, size, and position of the first region G1 are not particularly limited. The proportion of the area occupied by the first region G1 in the electrochemical cell 20 is not particularly limited, but it can be 10% or more and 50% or less, and preferably 15% or more and 40% or less. The electrochemical cell 20 of this embodiment includes a reaction prevention layer 25 between the solid electrolyte layer 24 and the air electrode 29. In this embodiment, the portion of the air electrode 29 located in the first region G1 upstream of the fuel gas flow direction 21D is designated as the first portion 81, and the portion of the air electrode 29 located in the second region G2 downstream of the fuel gas flow direction 21D is designated as the second portion 82. The thickness of the electrochemical cell 20 is not particularly limited, but may be, for example, 300 μm or more and 3 mm or less. The shape of the electrochemical cell 20 when viewed from above is not particularly limited, but may be, for example, a square with sides of 1 cm or more and 15 cm or less, a rectangle with long sides of 5 cm or more and 30 cm or less and short sides of 3 cm or more and 15 cm or less, or a circle with a diameter of 5 cm or more and 15 cm or less. An electrochemical cell stack 10 is formed by connecting a plurality of electrochemical cells 20 in series by an interconnector 16.

[0041] The fuel electrode 21 is formed using nickel oxide and oxide ion conductive ceramic particles as materials. The nickel oxide (NiO) used as the material for the fuel electrode 21 becomes nickel through a reduction process described later. The fuel electrode 21 in this embodiment is a porous, thin, plate-shaped fired body composed of nickel and YSZ (yttria-stabilized zirconia). Examples of ceramic materials having oxide ion conductivity include YSZ (yttria-stabilized zirconia), ScSZ (scandia-stabilized zirconia), (Gd,Ce)O2, i.e., GDC (gadolinium-doped ceria), (Sm,Ce)O2, i.e., SDC (samarium-doped ceria), and LaGaO3 (lanthanum gallate). The ceramic material contained in the fuel electrode 21 may be one type or two or more types. The thickness of the fuel electrode 21 is not particularly limited, but for example, it is 0.3 mm or more and 3 mm or less. In this embodiment, the thickness of the fuel electrode 21 is the largest among the thicknesses of the various components of the electrochemical cell 20, and the fuel electrode 21 functions as a support (support substrate, the most rigid component) of the electrochemical cell 20.

[0042] In the case of SOEC, the fuel electrode 21 functions as the cathode of the electrochemical cell 20. The fuel electrode 21 comprises, in order from the solid electrolyte layer 24 side, a fuel electrode functional layer 23 and a fuel electrode substrate layer 22. In this embodiment, the fuel electrode 21 includes, in order from the solid electrolyte layer 24 side, a fuel electrode functional layer 23 and a fuel electrode substrate layer 22 with a higher porosity than the fuel electrode functional layer 23. This ensures the strength of the fuel electrode functional layer 23. The thickness of the fuel electrode substrate layer 22 is preferably greater than that of the fuel electrode functional layer 23. The porosity of the fuel electrode functional layer 23 is not particularly limited, but for example, it is preferably 30% or less, more preferably 25% or less, and preferably 5% or more, and more preferably 10% or more. The porosity of the fuel electrode substrate layer 22 is not particularly limited, but for example, it is preferably 50% or less, more preferably 40% or less, and preferably 10% or more, and more preferably 20% or more. The fuel electrode 21 may be formed from a single layer instead of the fuel electrode functional layer 23 and the fuel electrode substrate layer 22.

[0043] The fuel electrode substrate layer 22 is a porous, plate-shaped sintered body containing a transition metal and an oxide ion conductive material. The fuel electrode substrate layer 22 may contain nickel (Ni) as the transition metal. The fuel electrode substrate layer 22 may contain zirconia-based materials such as yttria-stabilized zirconia (8YSZ, 10YSZ, etc.) or scandia-stabilized zirconia (ScSZ), ceria-based materials such as gadolinium-doped ceria (GDC: (Ce,Gd)O2) or samarium-doped ceria (SDC: (Ce,Sm)O2), or yttria (Y2O3) as the oxide ion conductive material. Note that 8YSZ refers to zirconia (ZrO2) containing 8 mol% yttria (Y2O3).

[0044] The thickness of the fuel electrode substrate layer 22 can be, for example, 0.2 mm or more and 5.0 mm or less. The thickness of the fuel electrode substrate layer 22 may be the largest among the components of the electrochemical cell 20 when the fuel electrode substrate layer 22 functions as a substrate. In the fuel electrode substrate layer 22, the volume ratio of Ni can be, for example, 20 vol% or more and 50 vol% or less, and the volume ratio of oxide ion conductive material can be, for example, 30 vol% or more and 60 vol% or less.

[0045] The fuel electrode functional layer 23 is positioned between the fuel electrode substrate layer 22 and the solid electrolyte layer 24. The fuel electrode functional layer 23 is a porous, plate-shaped sintered body containing a transition metal and an oxide ion conductive material. The fuel electrode functional layer 23 contains at least nickel (Ni) as the transition metal. The fuel electrode functional layer 23 may further contain iron (Fe) or copper (Cu) as the transition metal. The fuel electrode functional layer 23 includes zirconia-based materials such as yttria-stabilized zirconia (8YSZ, 10YSZ, etc.) and scandia-stabilized zirconia (ScSZ), or ceria-based materials such as gadolinium-doped ceria (GDC: (Ce,Gd)O2) and samarium-doped ceria (SDC: (Ce,Sm)O2) as the oxide ion conductive material.

[0046] The thickness of the fuel electrode functional layer 23 can be, for example, 1.0 μm or more and 30 μm or less. In the fuel electrode functional layer 23, the volume ratio of Ni can be, for example, 30 vol% or more and 60 vol% or less, and the volume ratio of oxide ion conductive material can be, for example, 40 vol% or more and 70 vol% or less.

[0047] As shown in Figures 5 and 6, the fuel gas flows on the surface of the fuel electrode 21 in the fuel gas flow direction 21D. The first region G1 is the region of the electrochemical cell 20 located upstream of the second region G2 in the fuel gas flow direction 21D. The second region G2 is the region of the electrochemical cell 20 located downstream of the first region G1 in the fuel gas flow direction 21D.

[0048] The solid electrolyte layer 24 is, for example, a solid oxide. The solid electrolyte layer 24 is a dense, thin, plate-like fired body. The solid electrolyte layer 24 is formed from solid oxides such as YSZ (yttria-stabilized zirconia), ScSZ (scandia-stabilized zirconia), SDC (samarium-doped ceria), GDC (gadolinium-doped ceria), and perovskite-type oxides. Examples of perovskite-type oxides include lanthanum gallate-based oxides having a perovskite-type structure. The thickness of the solid electrolyte layer 24 is not particularly limited, but is, for example, 3 μm to 30 μm.

[0049] In this embodiment, the solid electrolyte layer 24 is placed between the fuel electrode 21 and the reaction prevention layer 25. The solid electrolyte layer 24 has the function of allowing oxide ions generated in the air electrode 29 to pass through. The solid electrolyte layer 24 may contain zirconium (Zr), and the solid electrolyte layer 24 may contain Zr as zirconia (ZrO2). The solid electrolyte layer 24 may contain ZrO2 as its main component. In addition to ZrO2, the solid electrolyte layer 24 may also contain additives such as Y2O3 and / or Sc2O3. These additives function as stabilizers. In the solid electrolyte layer 24, the molar composition ratio of stabilizer to ZrO2 (stabilizer:ZrO2) is preferably about 3:97 to 20:80. That is, examples of materials for the solid electrolyte layer 24 include yttria-stabilized zirconia such as 3YSZ, 8YSZ, and 10YSZ, and zirconia-based materials such as ScSZ.

[0050] The air electrode 29 is placed on the reaction prevention layer 25. In the case of SOEC, the air electrode 29 functions as the anode of the electrochemical cell 20. The air electrode 29 contains a composite oxide having a perovskite structure. The composition of the composite oxide is given by general formula A1 x A2 y BO 3-δ(wherein 0.9≦x+y<1, δ is the amount of oxygen deficiency) is expressed. The ideal unit cell of a composite oxide having a perovskite structure is a cube, and when simply represented as ABO3, element A is located at the corners of the unit cell, element B is located at the body-centered position of the unit cell, and the oxygen element is located at the face-centered position of the unit cell. In this disclosure, the corner position of the unit cell where element A is located is called the "A site", and the body-centered position of the unit cell where element B is located is called the "B site", and two different elements, A1 and A2, are located at the A site. In this embodiment, the composition of A, B, and O in the composite oxide is not 1:1:3, but rather an A-site deficiency type perovskite structure. Specifically, an A-site deficiency type perovskite structure satisfies the condition 0.9≦x+y<1 in the above general formula. That is, x+y is less than 1. Since x+y is less than 1, the vacancies in the structure can increase the current density (high ionic conductivity). On the other hand, if x+y is less than 0.9, there will be many vacancies in the structure, resulting in insufficient strength. Also, in the above general formula, "O 3-δ The value δ, expressed as δ, represents the amount of oxygen deficiency, and this δ oxygen deficiency can also create voids in the structure. The δ oxygen deficiency does not need to exceed 0.1, and may even be 0. In other words, the oxygen deficiency is 0 ≤ δ ≤ 0.1. Similarly, if δ exceeds 0.1, the number of voids in the structure increases, resulting in insufficient strength.

[0051] Site A preferably contains at least one atom of La and Sr. Site B preferably contains at least one atom of Co and Fe. A specific example of such a composite oxide is, for example, the material for the air electrode 29, La x Sr y CoFeO 3-δ LSCF, which is (La,Sr)(Co,Fe)O3, and LSF, which is (La,Sr)FeO3, La x Sr y OO 3-δ LSC, or (La,Sr)CoO3, and LNF, or La(Ni,Fe)O3, are represented as Sm x Sr y OO 3-δExamples of materials include SSC represented by (Sm,Sr)CoO3, which is a composite oxide. These composite oxides are substances that possess both oxide ion conductivity and electronic conductivity, and are also called mixed conductive materials. In this embodiment, the air electrode 29 is lanthanum strontium cobalt ferrite LSCF (La 0.57 Sr 0.41 Co 0.2 Fe 0.8 O 2.99 It is a porous, thin, plate-like fired body formed from a material containing ).

[0052] The air electrode 29 contains a composite oxide having a perovskite structure as its "main component." Here, "contains as a main component" means that the composite oxide having a perovskite structure accounts for 60% by mass or more, preferably 70% by mass or more, and more preferably 90% by mass or more of the entire air electrode 29. The air electrode 29 may also contain components other than the composite oxide. Furthermore, the material of the air electrode 29 may be a powder (for example, with an average particle size of about 0.1 μm to 5 μm) or a crushed material (for example, with an average particle size of about 5 μm to 500 μm), or it may be a lump larger than the crushed material. The thickness of the air electrode 29 can be, for example, 5 μm or more and 150 μm or less.

[0053] The air electrode 29 may comprise an air electrode current collector layer and an air electrode functional layer. The air electrode current collector layer is of general type A1 x A2 y BO 3-δThe composite oxide has a perovskite structure represented by (where 0.9 ≤ x + y < 1, and δ is the oxygen deficiency). Such composite oxides are not particularly limited, but examples include LSCF, LSF, LSC, LNF, SSC, etc. The air electrode functional layer may contain components other than the composite oxide contained in the air electrode current collector layer. For example, the air electrode functional layer may be composited with the material of the solid electrolyte layer 24 (such as ceria or zirconia), which will be described later. The thickness of the air electrode current collector layer is not particularly limited, but for example, it may be 10 μm or more and 200 μm or less. The thickness of the air electrode functional layer is not particularly limited, but for example, it may be 5 μm or more and 20 μm or less. Note that the air electrode functional layer is not required. Furthermore, depending on the actual operating environment, the air electrode current collector layer may not be required.

[0054] In this embodiment, the air electrode 29 contains at least one of silicon, chromium, and sulfur as a "sub-component". In the following description, a substance containing silicon will also be called a "silicon-containing substance", a substance containing chromium will also be called a "chromium-containing substance", and a substance containing sulfur will also be called a "sulfur-containing substance". The silicon-containing substance is not particularly limited, but examples include silicon dioxide (SiO2). The chromium-containing substance is not particularly limited, but examples include strontium chromate (SrCrO4) and chromium oxide (Cr2O3). The sulfur-containing substance is not particularly limited, but examples include strontium sulfate (SrSO4). Here, the region occupied by the volume of the first part 81 of the air electrode 29 is referred to as the first volume. The region occupied by the volume of the second part 82 of the air electrode 29 is referred to as the second volume. The sum of the content of at least one of silicon, chromium, and sulfur in the first volume of the air electrode 29 is greater than the sum of the content of at least one of silicon, chromium, and sulfur in the second volume. The inventors have discovered that this can suppress the occurrence of cracks in the air electrode 29. Preferably, the total content of silicon, chromium, and sulfur inside the air electrode 29 is 0.001% by mass or more and 5.0% by mass or less. Preferably, this total content is 0.01% by mass or more and 5.0% by mass or less in the first volume, and preferably 0.001% by mass or more and 1.5% by mass or less in the second volume. The inventors have discovered that this can effectively suppress the occurrence of cracks in the air electrode 29. As a method for adjusting the content of silicon, chromium, and sulfur inside the air electrode 29, one method is to adjust the amount of silicon-containing material, chromium-containing material, and sulfur-containing material blended when manufacturing the air electrode 29. The content of silicon, chromium, and sulfur in the cross-section of the air electrode 29 is due to the amount of silicon-containing material, chromium-containing material, and sulfur-containing material blended into the air electrode 29, so the value in the first volume is approximately the same regardless of location, and the value in the second volume is also approximately the same regardless of location. Therefore, the sum of the silicon, chromium, and sulfur content in the cross-section of the air electrode 29 is expected to be between the value in the first volume and the value in the second volume.

[0055] The distribution of the main component, a composite oxide having a perovskite structure, and the silicon-containing material, chromium-containing material, and sulfur-containing material within the air electrode 29 is not particularly limited, but it is preferable that the composite oxide having a perovskite structure and the silicon-containing material, chromium-containing material, and sulfur-containing material are distributed substantially uniformly throughout. Furthermore, it is more preferable that the silicon-containing material, chromium-containing material, and sulfur-containing material are distributed between the particles of the composite oxide having a perovskite structure.

[0056] The method for calculating the total content of silicon, chromium, and sulfur in the cross-section of the air electrode 29 is described below. First, the cross-section of the air electrode 29 is precision mechanically polished, and then ion milling is performed on this cross-section using an IM4000PLUS manufactured by Hitachi High-Tech Corporation. Next, an EPMA (Electron Probe Micro Analyzer) is used to obtain the spectra of each elemental component, and the main component, silicon, chromium, and sulfur are identified. Subsequently, quantitative analysis of each element is performed on the EPMA's control computer based on sensitivity curve data constructed using standard samples, and the content of silicon, chromium, and sulfur in the air electrode 29 as a whole is calculated.

[0057] Such analyses were performed at five locations each within the first volume of the first part 81 and the second volume of the second part 82 of the air electrode 29. The arithmetic mean of the silicon, chromium, and sulfur content calculated at each of the five locations represents the silicon, chromium, and sulfur content in the first volume of the first part 81 and the second volume of the second part 82 of the air electrode 29.

[0058] Here, the analysis of the content within the first volume of the first part 81 and the second volume of the second part 82 shows the content within a predetermined volume. However, by measuring a portion of the cross-section in the thickness direction of the first part 81 and the second part 82 (the cross-sections shown in Figures 2 and 5) using EPMA or the like, it can be evaluated as substantially the same as the content in the entire first and second volumes. Therefore, in Table 1, the cross-sections in the thickness direction of the first part 81 and the second part 82 can be measured to determine the content in the first and second volumes, respectively.

[0059] In particular, as in this embodiment, when a first volume of the first part 81 and a second volume of the second part 82 are created, the silicon, chromium, and sulfur content in the cross-section of the air electrode 29 is due to the amount of silicon-containing material, chromium-containing material, and sulfur-containing material blended into the air electrode 29.

[0060] The above explains how to calculate the content of silicon, chromium, and sulfur, but the content of the main component, a complex oxide with a perovskite structure, can be calculated in the same way. When identifying a complex oxide with a perovskite structure, the atomic concentrations of the elements contained in the A1 site, the A2 site, the B site, and the oxygen element can be obtained, and the general formula A1 x A2 y BO 3-δ The composition ratios of A1, A2, B, and O are obtained for the following conditions (where 0.9 ≤ x + y < 1, and δ is the oxygen deficiency).

[0061] The air electrode 29 contains a substance containing at least one of silicon, chromium, and sulfur as a minor component. Suitable such substances are sulfates or composite oxides. Examples of sulfates include strontium sulfate (e.g., SrSO4). Examples of composite oxides include silicon dioxide (e.g., SiO2), chromium oxide (e.g., Cr2O3), and strontium chromate (e.g., SrCrO4). Such minor component substances have lower conductivity than the main component composite oxide having a perovskite structure. That is, the conductivity of the minor component compound is lower than that of the main component composite oxide having a perovskite structure. The minor component compound may also be insulating.

[0062] In this embodiment, "composing composition X as a minor component" means that substance Z accounts for 30% by mass or less of the total composition X, and more preferably 10% by mass or less.

[0063] Furthermore, the air electrode 29 contains a substance that includes at least one of silicon, chromium, and sulfur, as well as (Co,Fe)3O4(Co2FeO4, Co 1.5 Fe 1.5 It may also contain O4 and CoFe2O4, etc., Co3O4 (tricobalt tetroxide), or CoO (cobalt oxide), etc.

[0064] The first part 81 and the second part 82 differ in the composition ratio of the main component, a composite oxide having a perovskite structure, and the minor component, a substance.

[0065] The content of the main component perovskite structure composite oxide in the first volume of the first part 81 is smaller than the content of the main component perovskite structure composite oxide in the second volume of the second part 82. The perovskite structure composite oxide contained as the main component in the first volume of the first part 81 may be different from the perovskite structure composite oxide contained as the main component in the second volume of the second part 82, but it is preferable that they be the same.

[0066] The content of the minor component substance in the first volume of the first part 81 is greater than the content of the minor component substance in the second volume of the second part 82. The substance contained as a minor component in the first volume of the first part 81 may be different from the substance contained as a minor component in the second volume of the second part 82, but it is preferable that they be the same.

[0067] As the content of the minor components in the first part 81, a content within a volume of 10% to 90% of the thickness of the air electrode 29 from the surface 29A can be adopted. As the content of the minor components in the second part 82, a content within a volume of 10% to 90% of the thickness of the air electrode 29 from the surface 29A can be adopted.

[0068] Due to differences in thermal expansion coefficients, there is a risk that the air electrode 29 may delaminate from the solid electrolyte layer 24. As a countermeasure, there is a technique to place a composite material, which is an electrolyte mixed with the air electrode 29, between the air electrode 29 and the solid electrolyte layer 24. However, when a Zr (zirconium)-based material is used as the electrolyte material, if the air electrode 29 contains Sr (strontium), there is a problem in which SrZrO3 (hereinafter also called "SZO") is formed. In this case, for example, GDC (gadolinium-doped ceria) or SDC (samarium-doped ceria) is used as the electrolyte material to be mixed. Preferably, an intermediate layer, which is a mixture of electrolyte and composite oxide, can also be placed between the air electrode 29 and the solid electrolyte layer 24, and this intermediate layer is the air electrode functional layer.

[0069] When Sr contained in the air electrode 29 diffuses to the solid electrolyte layer 24, and this diffused Sr reacts with Zr contained in the solid electrolyte layer 24, a highly resistive substance called SZO is produced. If SZO is formed in layers in the region between the air electrode 29 and the solid electrolyte layer 24, the electrolytic performance decreases. To suppress the formation of such SZO, it is preferable to place a reaction prevention layer 25, for example, containing GDC, between the air electrode 29 and the solid electrolyte layer 24. This effectively suppresses the reaction of Sr diffused from the air electrode 29 with Zr contained in the solid electrolyte layer 24 to produce SZO. However, the electrochemical cell 20 does not necessarily have to be equipped with a reaction prevention layer 25. Examples of materials for the reaction prevention layer 25 include ceria-based materials containing cerium (Ce) and rare earth metal oxides dissolved in Ce. The reaction prevention layer 25 is not particularly limited, but is preferably a dense, thin, plate-like fired body made of ceria, for example. Examples of ceria are not particularly limited, but include GDC, SDC, etc.

[0070] In this embodiment, the reaction prevention layer 25 is placed between the solid electrolyte layer 24 and the air electrode 29. The reaction prevention layer 25 has the function of suppressing the formation of a high-resistance layer between the solid electrolyte layer 24 and the air electrode 29. The thickness of the reaction prevention layer 25 can be, for example, 1 μm or more and 20 μm or less.

[0071] (Configuration of air electrode 29) The configuration of the air electrode 29 will be described with reference to Figures 5 and 6. Figure 5 is a schematic diagram illustrating the reaction unit 11. As shown in Figure 5, the first portion 81, located in the first region G1 of the electrochemical cell 20, is the portion of the air electrode 29 upstream of the second portion 82 in the fuel gas flow direction 21D. In this embodiment, the first portion 81 is located upstream of the center line CL in the fuel gas flow direction 21D of the air electrode 29. However, the first portion 81 only needs to be located upstream of the second portion 82, and the shape, size, and position of the first portion 81 are not particularly limited. The proportion of the air electrode 29 occupied by the first portion 81 is not particularly limited, but it can be 10% or more and 50% or less, and preferably 15% or more and 40% or less. In this embodiment, the first portion 81 is located upstream of the second portion 82 in the direction in which the oxidizer gas flows inside the air chamber 35. The oxidizing gas may flow through the air chamber 35 from passage 15d to passage 15c. In other words, the first part 81 may be located downstream of the second part 82 in the direction in which the oxidizing gas flows through the air chamber 35.

[0072] Figure 6 is a plan view of the surface 29A of the air electrode 29. Surface 29A is the surface of the air electrode 29 opposite to the solid electrolyte layer 24. Surface 29A has a first surface A1 and a second surface A2. The first surface A1 is the surface of the first portion 81 and is the surface of surface 29A located on the upstream side in the fuel gas flow direction 21D. The second surface A2 is the surface of the second portion 82 and is the surface of surface 29A located on the downstream side in the fuel gas flow direction 21D.

[0073] The first surface A1 is the surface portion of surface 29A upstream of the centerline CL on surface 29A in the fuel gas flow direction 21D. However, the first surface A1 only needs to be located upstream of the second surface A2, and the shape, size, and position of the first surface A1 are not particularly limited. The area ratio occupied by the first surface A1 on surface 29A is not particularly limited, but it can be 10% or more and 50% or less, and preferably 15% or more and 40% or less. By setting the area ratio occupied by the first surface A1 on surface 29A as described above, a balance can be achieved between pressure resistance and gas diffusivity.

[0074] The first part 81 comprises a main component composed of a composite oxide having a perovskite structure and a secondary component composed of a substance containing at least one of silicon, chromium, and sulfur.

[0075] The second portion 82 is the part of the air electrode 29 located downstream of the first portion 81 in the fuel gas flow direction 21D. In this embodiment, the second portion 82 is located downstream of the centerline CL in the fuel gas flow direction 21D of the air electrode 29. However, the second portion 82 only needs to be located downstream of the first portion 81, and the shape, size, and position of the second portion 82 are not particularly limited. The proportion that the second portion 82 occupies in the air electrode 29 is not particularly limited, but it can be 50% or more and 90% or less, and preferably 60% or more and 85% or less.

[0076] The second surface A2 is the portion of the surface 29A downstream of the centerline CL on the surface 29A in the fuel gas flow direction 21D. However, the second surface A2 only needs to be located downstream of the first surface A1, and the shape, size, and position of the second surface A2 are not particularly limited. The area ratio occupied by the second surface A2 on the surface 29A is not particularly limited, but it can be 50% to 90%, and preferably 60% to 85%.

[0077] The second part 82 comprises a main component composed of a composite oxide having a perovskite structure.

[0078] By supplying water vapor to the fuel electrode 21 and an oxygen-containing gas to the air electrode 29 of the SOEC electrochemical cell 20, and by passing an electric current between the fuel electrode 21 and the air electrode 29, the chemical reactions shown in equations (1) and (2) below occur. As a result, hydrogen is generated from the fuel electrode 21 and oxygen is generated from the air electrode 29. Note that oxide ions (O) generated at the fuel electrode 21 2- ) passes through the interior of the solid electrolyte layer 24 and moves to the air electrode 29. H2O + 2e - →H2+O 2- (At: Fuel electrode 21) …(1) O 2- →(1 / 2)·O2+2e - (At: Air pole 29) …(2)

[0079] Here, the fuel gas concentration tends to be higher on the surface of the fuel electrode 21 located in the first region G1 upstream of the fuel gas flow direction 21D compared to the surface of the fuel electrode 21 located in the second region G2 downstream. For this reason, the chemical reaction shown in equation (1) above is more likely to occur in the portion of the fuel electrode 21 located in the first region G1 than in the portion located in the second region G2. Oxide ions (O) produced by the chemical reaction shown in equation (1) 2- Based on the oxygen conductivity of the solid electrolyte, the oxide ions move to the air electrode 29, and based on the moved oxide ions, the chemical reaction shown in equation (2) above occurs at the air electrode 29. That is, oxygen is generated at the air electrode 29.

[0080] As mentioned above, the first part 81 is the portion of the air electrode 29 located upstream in the fuel gas flow direction 21D. The second part 82 is the portion of the air electrode 29 located downstream in the fuel gas flow direction 21D. For this reason, the amount of oxide ions supplied to the air electrode 29 via the solid electrolyte layer 24 tends to be greater in the first part 81 than in the second part 82. Also, the chemical reaction shown in equation (2) is more likely to occur in the first part 81 than in the second part 82. In other words, the amount of oxygen generated in the first part 81 of the air electrode 29 tends to be greater than the amount of oxygen generated in the second part 82. For this reason, in the first part 81 of the air electrode 29 and its surface, the first surface A1, to which more oxide ions reach via the solid electrolyte layer 24, the gas pressure is greater than in the second part 82 and its surface, the second surface A2, and it is thought that cracks are more likely to occur due to the pressure difference. Therefore, in this embodiment, the content of minor components in the first volume of the first part 81 is made greater than the content of minor components in the second volume of the second part 82. This improves the bonding strength between particles of the main component in the first volume of the first part 81, thereby suppressing the occurrence of cracks and, consequently, improving the durability of the air electrode 29.

[0081] The content of minor components in the first volume of the first part 81 can be 0.01% by mass or more and 5.0% by mass or less, and more preferably 0.02% by mass or more and 3.0% by mass or less. The content of major components in the first volume of the first part 81 can be 95.0% by mass or more, and preferably 97.0% by mass or more.

[0082] The content of minor components in the second volume of the second part 82 can be 0.001% by mass or more and 1.5% by mass or less, and more preferably 0.003% by mass or more and 1.5% by mass or less. The content of the main component in the second volume of the second part 82 can be 98.5% by mass or more.

[0083] The main component of the air electrode 29 is a composite oxide having a perovskite structure, La x Sr y OO 3-δ (LSC) or La x Sr y CoFeO 3-δ In the case of (LSCF), the ratio of the content of the minor component in the second volume of the second part 82 to the ratio of the content of the minor component in the first volume of the first part 81 is preferably 0.1 or more and 0.9 or less. The composite oxide having a perovskite structure, which is the main component of the air electrode 29, is Sm x Sr y OO 3-δ In the case of (SSC), it is preferable that the content of the minor component in the second volume of the second portion 82 is 0.1 or more and 0.9 or less relative to the content of the minor component in the first volume of the first portion 81.

[0084] In this SOEC electrochemical cell 20, conductive connecting members (interconnectors 16) for collecting current are typically joined and fixed to the fuel electrode 21 and the air electrode 29 using a bonding agent, and a potential difference is applied through each interconnector 16 to allow current to flow. Hydrogen gas generated from the fuel electrode 21 is then collected.

[0085] The fuel electrode 21 is supplied with a fuel gas containing water vapor, for example, 20 liters / (min·cm). 2 ) Over 140 liters / (minute·cm) 2 It may also be supplied and used at a flow rate of 25 liters / (min·cm²) or less. 2 ) Over 130 liters / (minute·cm) 2 )The fuel may be supplied and used at the following flow rates.In the case of co-electrolysis, a gas containing water vapor and CO2 may be supplied as the fuel gas.In addition, in a stack in which cells are stacked in multiple stages, the amount of fuel gas supplied by blowers, pumps, etc. will naturally increase by the number of stacks.

[0086] At the air electrode 29, an oxygen-containing gas is supplied, for example, 20 liters / (min·cm). 2 ) 60 liters / (min·cm) 2 It may also be supplied and used at a flow rate of 30 liters / (min·cm²) or less. 2 ) 50 liters / (min·cm) 2 )The gas may be supplied and used at the following flow rates. As the oxygen-containing gas, oxygen gas may be used, or air may be used. In a stack in which cells are stacked in multiple stages, the amount of gas supplied to the air electrode 29 side by blowers, pumps, etc. will naturally increase by the number of stacks.

[0087] The volume of the air chamber 35 facing the air pole 29 is not particularly limited, but is 8 cm³. 3 13cm or more 3 Preferably, it is 9cm 3 More than 11cm 3 The following is more preferable. Here, the volume of the air chamber 35 that the air electrode 29 faces refers to the volume per cell, and means the volume excluding the portion occupied by the current collector AC1, etc.

[0088] (Manufacturing method) Next, an example of a manufacturing method for the electrochemical cell 20 will be described. The various conditions such as materials, particle size, temperature, and coating method described below can be appropriately changed depending on the manufacturing environment. In the following description, "molded body" refers to the state before firing.

[0089] (Fabrication of green sheets for fuel electrode substrate layers) A slurry is prepared by adding organic beads (a pore-forming material), butyral resin, DOP (a plasticizer), Florene G-700 (a dispersant), and a mixed solvent of toluene and ethanol to a mixed powder of NiO powder and YSZ powder and mixing them in a ball mill. The organic beads are spherical particles formed from polymers such as polymethyl methacrylate or polystyrene. The obtained slurry is thinned using the doctor blade method to produce a green sheet for the fuel electrode substrate layer with a predetermined thickness (e.g., about 200 μm to 300 μm). The mixing ratio of NiO powder and YSZ powder when producing the green sheet for the fuel electrode can be set as appropriate, as long as the performance is satisfied. For example, the mixing ratio of NiO powder to YSZ powder may be 20% to 50% by volume for NiO and 30% to 60% by volume for YSZ.

[0090] (Preparation of green sheets for the fuel electrode functional layer) A slurry is prepared by adding butyral resin, the plasticizer DOP, the dispersant Florene G-700, and a mixed solvent of toluene and ethanol to a mixed powder of NiO powder and YSZ powder and mixing them in a ball mill. The obtained slurry is thinned using the doctor blade method to produce a green sheet for the fuel electrode functional layer with a predetermined thickness (e.g., about 5 μm to 50 μm). The mixing ratio of NiO powder and YSZ powder when producing the green sheet for the fuel electrode functional layer can be set as appropriate, as long as the performance is satisfied. For example, the mixing ratio of NiO powder and YSZ powder may be 30% to 60% by volume for NiO and 40% to 70% by volume for YSZ.

[0091] (Preparation of green sheets for solid electrolyte layers) To the YSZ powder, butyral resin, the plasticizer DOP, the dispersant Florene G-700, and a mixed solvent of toluene and ethanol are added and mixed in a ball mill to prepare a slurry. The obtained slurry is thinned using the doctor blade method to produce a green sheet for the solid electrolyte layer of a predetermined thickness (e.g., 10 μm).

[0092] (Fabrication of a laminate consisting of a solid electrolyte layer 24, a fuel electrode functional layer 23, and a fuel electrode substrate layer 22) The green sheet for the fuel electrode substrate layer, the green sheet for the fuel electrode functional layer, and the green sheet for the solid electrolyte layer are bonded together and degreased at a predetermined temperature (e.g., approximately 280°C). Furthermore, the laminate of degreased green sheets is fired at a predetermined temperature (e.g., approximately 1350°C). This yields a laminate of the solid electrolyte layer 24, the fuel electrode functional layer 23, and the fuel electrode substrate layer 22.

[0093] The method for manufacturing the cell is not limited to this method; the following methods may also be used. A slurry is prepared by adding polyvinyl alcohol (PVA) as a binder to a mixture of NiO powder and YSZ powder. This slurry is dried and granulated in a spray dryer, and a molded body of the fuel electrode 21 is formed by a die press molding method. Next, water and a binder are added to the YSZ powder, and this mixture is mixed in a ball mill for 24 hours to prepare a slurry. This slurry is then applied and molded onto the molded body of the fuel electrode 21 to laminate and form a molded body of the solid electrolyte layer 24. This laminate of molded bodies is co-sintered in an electric furnace (in an oxygen-containing atmosphere) in air, for example at 1350°C, to form a laminate of the fuel electrode 21 and the solid electrolyte layer 24. When forming the film that will later become the solid electrolyte layer 24 on the fuel electrode 21, methods such as tape lamination or printing may be used.

[0094] (Formation of reaction prevention layer 25) Next, a reaction prevention layer 25 is formed. Specifically, polyvinyl alcohol as an organic binder and butyl carbitol as an organic solvent are added to GDC powder and mixed, and the viscosity is adjusted to prepare a paste for the reaction prevention layer. The obtained paste for the reaction prevention layer is applied to the surface of the solid electrolyte layer 24 side of the laminate of the solid electrolyte layer 24 and the fuel electrode 21, for example by screen printing, and fired at, for example, 1180°C. This forms the reaction prevention layer 25, and a laminate of the fuel electrode 21, the solid electrolyte layer 24 and the reaction prevention layer 25 (hereinafter referred to as the "intermediate laminate") is produced.

[0095] (Formation of the first part 81 of the air electrode 29) Next, the air electrode 29 is formed. First, LSCF powder and at least one of the following in specified amounts—silicon dioxide (SiO2) as a silicon-containing substance, strontium sulfate (SrSO4) as a sulfur-containing substance, and strontium chromate (SrCrO4) as a chromium-containing substance—are mixed with polyvinyl alcohol as an organic binder and butyl carbitol as an organic solvent to adjust the viscosity and prepare the first part paste. Next, the prepared first part paste is applied to the surface of the reaction prevention layer 25 side of the intermediate laminate, for example by screen printing, and dried to form the first part 81 of the air electrode 29.

[0096] (Formation of the second part 82 of the air electrode 29) Next, the LSCF powder and at least one of the following substances—silicon dioxide (SiO2) as a silicon-containing substance, strontium sulfate (SrSO4) as a sulfur-containing substance, and strontium chromate (SrCrO4) as a chromium-containing substance—are mixed with polyvinyl alcohol as an organic binder and butyl carbitol as an organic solvent to adjust the viscosity and prepare the paste for the second part. At this time, the content of at least one of the substances—silicon dioxide (SiO2), strontium sulfate (SrSO4) as a sulfur-containing substance, and strontium chromate (SrCrO4) as a chromium-containing substance—is set lower than the content of silicon dioxide, strontium sulfate, and strontium chromate in the paste for the first part. Next, the paste for the second part is applied to the surface on the reaction prevention layer 25 side, avoiding the molded body of the first part 81 formed on the surface on the reaction prevention layer 25 side, thereby forming the molded body of the second part 82 of the air electrode 29. With the above steps, the molded body of the air electrode 29 is completed.

[0097] (Firing of air electrode 29) The intermediate laminate, to which the first and second partial pastes have been applied, is fired at a predetermined firing temperature (e.g., 1100°C). Subsequently, this firing process forms the air electrode 29, and a laminate of the fuel electrode substrate layer 22, the fuel electrode functional layer 23, the solid electrolyte layer 24, the reaction prevention layer 25, and the air electrode 29, i.e., a single cell of the electrochemical cell 20, is created.

[0098] (Other embodiments) The present invention is not limited to the embodiments described above, and various modifications or changes are possible without departing from the scope of this disclosure.

[0099] (A) In the above embodiment, the air electrode 29 has a first portion 81 and a second portion 82, but it may also have a base portion 26 that supports the first portion 81 and the second portion 82, as in the air electrode 129 of the electrochemical cell 120 of other embodiments shown in Figures 7(a) and 7(b). The base portion 26 is made of a material of general formula A1 x A2 y BO3-δ The main component is a composite oxide having a perovskite structure represented by (where 0.9 ≤ x + y < 1, and δ is the amount of oxygen deficiency), and it contains a solid electrolyte. The thickness of the base portion 26 is not particularly limited, but it can be 1% to 30% of the thickness of the air electrode 29, and preferably 5% to 20%.

[0100] An air electrode 129 having a base portion 26 can be prepared as follows. First, a paste for the base portion is prepared by adding polyvinyl alcohol as an organic binder and butyl carbitol as an organic solvent to a powder containing LSCF powder, GDC powder, and a powder containing at least one of silicon, chromium, and sulfur, and mixing the mixture to adjust the viscosity. The content of the auxiliary components is prepared to be the same as that of the second portion 82. Next, the prepared paste for the base portion is applied to the surface of the reaction prevention layer 25 on the intermediate laminate side, for example by screen printing, and dried. Next, the molded body of the first portion 81 is formed at a predetermined position on the surface of the molded body of the base portion 26, and the molded body of the second portion 82 is formed in the area where the surface of the molded body of the base portion 26 is exposed. After that, the molded bodies of the first portion 81, the second portion 82, and the base portion 26 are fired at a predetermined firing temperature (for example, 1100°C).

[0101] Thus, even when the air electrode 129 has a first portion 81, a second portion 82, and a base portion 26, the bonding strength between the main component particles of the first portion 81 of the air electrode 129 can be improved, thereby suppressing the occurrence of cracks in the air electrode 129.

[0102] (B) In the above embodiment, the air electrode 29 has a first portion 81 and a second portion 82, but the air electrode 29 may include portions other than the first portion 81 and the second portion 82. For example, as in the air electrode 229 of the electrochemical cell 220 of another embodiment shown in Figures 8(a) and 8(b), the air electrode 229 may have a base portion 226 that supports the first portion 81 and the second portion 82. The base portion 226 is made of a material of general formula A1 x A2 y BO3-δ The main component is a composite oxide having a perovskite structure represented by (where 0.9 ≤ x + y < 1, and δ is the oxygen deficiency), and it contains a solid electrolyte. The base portion 226 has a recess 226A that accommodates the first portion 81 and the second portion 82. The surface 229A of the air electrode 229 includes the first surface A1 of the first portion 81, the second surface A2 of the second portion 82, and the third surface A3 of the base portion 226. Thus, the surface 229A of the air electrode 229 may include surfaces other than the first surface A1 and the second surface A2. The thickness of the base portion 226 is not particularly limited, but it can be 1% to 30% of the thickness of the air electrode 229, and preferably 5% to 20%.

[0103] An air electrode 229 having a base portion 226 can be prepared as follows. First, a paste for the base portion is prepared by mixing a powder containing LSCF powder, GDC powder, and a powder containing at least one of silicon, chromium, and sulfur with polyvinyl alcohol as an organic binder and butyl carbitol as an organic solvent, and adjusting the viscosity. The content of the auxiliary components is prepared to be the same as that of the second portion 82. Next, the prepared base portion paste is uniformly applied to the surface of the intermediate laminate on the reaction prevention layer 25 side, and then applied in a predetermined pattern to form a recess 226A, thereby forming a molded body of the base portion 226. Next, a molded body of the first portion 81 is formed in half of the recess 226A of the base portion 226, and a molded body of the second portion 82 is formed in the remaining half. After that, the molded bodies of the first portion 81, the second portion 82, and the base portion 226 are fired at a predetermined firing temperature (e.g., 1100°C).

[0104] Thus, even when the air electrode 229 has a first portion 81 and a second portion 82 and a base portion 226, the bonding strength between the particles of the main component of the first portion 81 of the air electrode 229 can be improved, thereby suppressing the occurrence of cracks in the air electrode 229.

[0105] (C) In the above embodiment, the first surface A1 of the first part 81 and the second surface A2 of the second part 82 are adjacent on the surface 29A of the air electrode 29, but they may be separated from each other. For example, as in the air electrode 329 of the electrochemical cell 320 of another embodiment shown in Figures 9(a) and 9(b), the air electrode 329 may have a base portion 326 that supports the first part 81 and the second part 82. The base portion 326 is based on general formula A1 x A2 y BO 3-δ The composite oxide having a perovskite structure represented by (where 0.9 ≤ x + y < 1, and δ is the oxygen deficiency) is the main component and contains a solid electrolyte. The base portion 326 has a first recess 326A that accommodates the first portion 81 and a second recess 326B that accommodates the second portion 82. The surface 329A of the air electrode 329 includes the first surface A1 of the first portion 81, the second surface A2 of the second portion 82, and the fourth surface A4 of the base portion 326. The fourth surface A4 is located between the first surface A1 and the second surface A2. The thickness of the base portion 326 is not particularly limited, but it can be 1% to 30% of the thickness of the air electrode 329, and preferably 5% to 20%.

[0106] An air electrode 329 having a base portion 326 can be manufactured as follows. First, a paste for the base portion is prepared by mixing a powder containing LSCF powder, GDC powder, and a powder containing at least one of silicon, chromium, and sulfur with polyvinyl alcohol as an organic binder and butyl carbitol as an organic solvent, and adjusting the viscosity. The content of the auxiliary components is prepared to be the same as that of the second portion 82. Next, the prepared base portion paste is uniformly applied to the surface of the intermediate laminate on the reaction prevention layer 25 side, and then a molded body of the base portion 326 is formed by applying it in a predetermined pattern to form the first recess 326A and the second recess 326B. Next, a molded body of the first portion 81 is formed in the first recess 326A, and a molded body of the second portion 82 is formed in the second recess 326B. After that, the molded bodies of the first portion 81, the second portion 82, and the base portion 326 are fired at a predetermined firing temperature (e.g., 1100°C).

[0107] Thus, even when the air electrode 329 has a first portion 81 and a second portion 82 and a base portion 326, the bonding strength between the particles of the main component of the first portion 81 of the air electrode 329 can be improved, thereby suppressing the occurrence of cracks in the air electrode 329. In these other embodiments, the base portions 26, 226, and 326 may be the air electrode functional layers described above.

[0108] Subsequently, a reduction process is performed to reduce the fuel electrode 21 (i.e., to reduce the NiO contained in the fuel electrode 21 to Ni) in order to make the electrochemical cell 20 ready for hydrogen production operation. The reduction process is achieved, for example, by exposing the fuel electrode 21 to a hydrogen atmosphere at a predetermined temperature for a predetermined time. The reducing gas used in the reduction process is not limited to hydrogen, but may be other gases such as methane gas, and the concentration of the reducing gas is also not limited. As a reducing gas with a reducing agent concentration of less than 100% by volume, for example, nitrogen gas may be included in addition to hydrogen gas.

[0109] (Explanation of effects) As described above, the air electrodes 29,129,229,329 of the above configuration contain a composite oxide having a perovskite structure as the main component and a secondary component containing at least one of silicon, chromium, and sulfur. The electrochemical cell 20 has a first region G1 and a second region G2 located downstream of the first region G1 in the fuel gas flow direction 21D through which the fuel gas flows. The content of the secondary component in the first volume of the first portion 81 of the air electrodes 29,129,229,329, which is located in the first region G1, is greater than the content of the secondary component in the second volume of the second portion 82 of the air electrodes 29,129,229,329, which is located in the second region G2.

[0110] The inventors have found that by using such air electrodes 29,129,229,329, the occurrence of cracks in the air electrodes 29,129,229,329 can be suppressed. As a result, a decrease in current density at the thermal neutral point (1.3V) can be suppressed. Furthermore, as a result, an electrochemical cell 20 that can operate for a long period of time can be provided. The mechanism by which the above-described air electrodes 29,129,229,329 suppress the occurrence of cracks in the air electrodes 29,129,229,329 is not clear, but the following presumed mechanism is possible. That is, by preparing at least one of silicon, chromium, and sulfur in the above-described content ratio, the sinterability is improved by filling the gaps between the particles of the composite oxide having a perovskite structure, and as a result, the bonding force between particles in the air electrodes 29,129,229,329 is strengthened.

[0111] Furthermore, silicon-containing materials, chromium-containing materials, and sulfur-containing materials are substances that do not contribute to the reactions at air electrodes 29, 129, 229, and 329. If the content of at least one of the silicon-containing material, chromium-containing material, and sulfur-containing material is greater in the second volume of the second part 82 than in the first volume of the first part 81, it is considered that the inert portion that does not contribute to the reactions at air electrodes 29, 129, 229, and 329 will be greater in the second volume of the second part 82 than in the first volume of the first part 81. As a result, the reaction field in the second part 82 in which the chemical reaction shown in equation (2) above occurs will decrease, and the current density will decrease, which is considered undesirable. It is also considered that the higher the content of at least one of the silicon-containing material, chromium-containing material, and sulfur-containing material at air electrodes 29, 129, 229, and 329, the more the sinterability will improve and the number of cracks will decrease. However, if the content of at least one of the silicon-containing material, chromium-containing material, and sulfur-containing material is greater in the second volume of the second part 82 than in the first volume of the first part 81, the bonding force of the second part 82 becomes stronger than the bonding force of the first part 81, leading to increased strain, which in turn increases cracks in the first part 81 and reduces the current density, which is considered undesirable.

[0112] The following describes the tests that confirmed the suppression of crack formation in the air electrode 29 in the above configuration.

[0113] (test) In this test, for the SOEC (electrochemical cell 20) according to the above embodiment, multiple types of test specimens (fired bodies) were used, in which the content of minor components in the first volume of the first part 81 and the second volume of the second part 82 of the air electrode 29 was varied. Specifically, as shown in Table 1, 22 different levels of samples No. 1 to 22 were prepared, and one test specimen was made for each level. Table 1 shows the results of evaluating the main component of the air electrode 29, the type of minor component, the content rate of the minor component in the first volume of the first part 81, the content rate of the minor component in the second volume of the second part 82, the content rate of the minor component in the second volume of the second part 82 relative to the content rate of the minor component in the first volume of the first part 81, the current density at the thermal neutral point, and the presence or absence of crack formation for each sample from No. 1 to No. 22. In this experiment, SiO2 was used as the silicon-containing material, SrCrO4 and Cr2O3 as the chromium-containing materials, and SrSO4 as the sulfur-containing material.

[0114] In these test specimens, the thickness of the air electrode 29 was kept constant at 100 μm, the thickness of the fuel electrode 21 at 500 μm, and the thickness of the solid electrolyte layer 24 (8YSZ) at 10 μm. Furthermore, the shape of these test specimens, viewed from above, was a 10 cm square. The types and amounts of the by-components in the air electrode 29 were prepared during the manufacturing of the air electrode 29. Hydrogen was used as the reducing agent in the reducing gas. The reducing gas with a reducing agent concentration of 100% by volume consisted solely of hydrogen. Air was used in the air electrode 29 during the reduction process.

[0115] Using the test specimens prepared in this manner, the current density at 1.3V under 700°C was measured, and all initial performance values ​​were 0.75A / cm². 2 More than 1A / cm 2 I confirmed the following:

[0116] Subsequently, these test specimens underwent the following thermal cycle electrolysis test using an infrared lamp. Specifically, the test specimens were heated from room temperature (25°C) to 700°C in 10 minutes, then cooled from 700°C to room temperature in 30 minutes. This process was repeated 50 times, and the current density at 1.3V was measured again at 700°C. The results are shown in Table 1. Then, SEM (Scanning Electron Microscope) observations were performed on 20 fields of view of the cross-section within the first volume of the first part 81 of each test specimen that underwent this thermal cycle electrolysis test. In the evaluation results, the denominator represents the total number of test specimens, and the numerator represents the number of test specimens with cracks. Based on this, a comprehensive evaluation was performed using current density and the presence or absence of cracks as criteria.

[0117] (result) The evaluation results are shown in Table 1.

[0118] [Table 1]

[0119] In Table 1, samples No. 2-5, No. 8-11, and No. 15-18 are examples. Samples No. 1, No. 6, No. 7, No. 12-14, and No. 19-22 are comparative examples.

[0120] As shown in Table 1, General formula A1 x A2 y BO 3-δ(where 0.9≦x+y<1, and δ is the oxygen deficiency amount) as the main component, and in the content of at least one of silicon, chromium, and sulfur in the air electrode 29, when the content of the subcomponent in the first volume of the first portion 81 disposed in the first region G1 on the upstream side in the fuel gas flow direction 21D is greater than the content of the subcomponent in the second volume of the first portion 81 disposed in the second region G2 on the downstream side in the fuel gas flow direction 21D, no occurrence of cracks was confirmed in the first portion 81 (Samples 2-5, 8-11, 15-18, 20). Regarding Sample 20, x+y=1, which does not satisfy x+y<1. In this case, no occurrence of cracks was confirmed in the first portion 81, but the desired current density was not obtained. This is presumed to be because no deficiency occurs at the A-site of the perovskite structure, so the current density derived from the deficient structure cannot be obtained. Regarding Sample 22, x+y=0.89, which does not satisfy 0.9≦x+y. In this case, occurrence of cracks was confirmed in the first portion 81. This is presumed to be because as the deficiency amount at the A-site of the perovskite structure increases, the number of vacancies in the structure increases, and the strength required for the first portion 81 cannot be obtained.

[0121] Further, the main component of the air electrode 29 is La x Sr y CoO 3-δ LSC represented by or La x Sr y CoFeO 3-δ LSCF represented by, when the content of the subcomponent in the second volume of the second portion 82 relative to the content of the subcomponent in the first volume of the first portion 81 is 0.1 or more and 0.9 or less, it was found that the occurrence of cracks in the first portion 81 of the air electrode 29 is suppressed compared to other cases (Samples 2-5, 8-11).

[0122] Further, the main component of the air electrode 29 is Sm x Sr y CoO 3-δIn the case of an SSC represented by [formula], when the content of the minor component in the second volume of the second part 82 is 0.1 or more and 0.9 or less relative to the content of the minor component in the first volume of the first part 81, it was found that the occurrence of cracks in the first part 81 of the air electrode 29 is suppressed compared to other cases (Samples 15-18).

[0123] Furthermore, it was found that when the total content of at least one of silicon, chromium, and sulfur in the air electrode 29 is 0.01% by mass or more and 5.0% by mass or less in the first volume of the first part 81, and 0.001% by mass or more and 1.5% by mass or less in the second volume of the second part 82, the current density tends to be higher compared to other cases (Samples 2-5, 8-11, 15-18). Furthermore, it was found that the current density tends to be even higher when the total content of at least one of silicon, chromium, and sulfur in the air electrode 29 is 0.02% by mass or more and 3.0% by mass or less in the first volume of the first part 81, and 0.003% by mass or more and 1.5% by mass or less in the second volume of the second part 82 (Samples 2, 3, 8, 9, 15, 16).

[0124] This disclosure is not limited to the embodiments described above, and can be implemented in various configurations without departing from its spirit. For example, the technical features in the embodiments corresponding to the technical features in each form described in the summary of the invention can be replaced or combined as appropriate to solve some or all of the above-described problems, or to achieve some or all of the above-described effects. Furthermore, if a technical feature is not described as essential in this specification, it can be deleted as appropriate.

[0125] The electrochemical cell 20 only needs to have a fuel electrode 21, a solid electrolyte layer 24, and an air electrode 29, and the presence or absence of other components, the shape, material, dimensions, etc. of each component can be changed. For example, the configuration of the electrochemical cell 20 may be changed as follows. (1) The shape of the electrochemical cell 20 may be, for example, a fuel electrode support type, a flat plate type, a cylindrical type, a flattened type, a vertical stripe type, a horizontal stripe type, a single-end supported stack type, a double-end supported stack type, etc. The cross-section of the cell may also be elliptical. (2) In the above embodiment, the electrochemical cell 20 is provided with a reaction prevention layer 25, but it is not necessary to provide a reaction prevention layer 25. (3) In the above embodiment, the reaction prevention layer 25 is a single layer structure, but it may also be a multi-layer structure in which a dense reaction prevention layer 25 and a porous reaction prevention layer 25 are laminated (in any order). (4) In the reaction unit 11, in order to discharge the oxygen generated at the air electrode 29 from the air chamber 35 via the passage 15d, the oxidizing gas is supplied to flow inside the air chamber 35 from passage 15c to passage 15d. Alternatively, the reaction unit 11 may be configured such that passage 15c is not provided and the oxygen generated at the air electrode 29 is drawn in from passage 15c. Note that if the oxygen concentration in the air chamber 35 is too high, it may affect the piping connected to passage 15d, so it is preferable that the oxidizing gas is supplied to the inside of the air chamber 35 so that it flows from passage 15c to passage 15d. (5) The electrochemical cell 20 can be of any type as long as it is a solid oxide type electrolytic cell. That is, the electrochemical cell 20 may be configured to function as a single SOFC cell. Also, the electrochemical cell 20 may be configured to have the functions of both an SOEC and an SOFC, i.e., to function reversibly. (6) The electrochemical cell 20 may be used as a solid oxide fuel cell or as a solid oxide electrolytic cell. (7) The configurations listed as different forms can be combined with each other. [Explanation of Symbols]

[0126] 10…Electrochemical cell stack, 11…Reaction unit, 12,13…End plate, 14…Bolt, 15a,15b,15c,15d…Passage, 16…Interconnector, 17…Fuel electrode frame, 19…Air electrode frame, 20,120,220,320…Electrochemical cell, 21…Fuel electrode, 21D…Fuel gas flow direction, 22…Fuel electrode substrate layer, 23…Fuel electrode functional layer, 24…Solid electrolyte layer, 24a…Surface, 25…Reaction prevention layer, 26,226,326…Base portion, 29,129,229 ,329…Air electrode, 29A,229A,329A…Surface, 30…Separator, 31…Brazing material, 33…Fuel chamber, 35…Air chamber, 37…Opening, 47…Electrochemical cell with separator, 52,53…Terminal plate, 60…Hydrogen production device, 61…Hot module, 62…Vaporizer, 63…Heat exchanger, 64…Heater, 65…Insulation material, 66…Condenser, 81…First part, 82…Second part, A1…First surface, A2…Second surface, AC1,FC1…Current collector, G1…First region, G2…Second region

Claims

1. General form A1 x A2 y BO 3-δ An air electrode containing a composite oxide having a perovskite structure represented as (where 0.9 ≤ x + y < 1, δ is the amount of oxygen deficiency), The fuel electrode to which fuel gas is supplied, A solid electrolyte layer is disposed between the air electrode and the fuel electrode, An electrochemical cell comprising, The aforementioned air electrode is It contains at least one of silicon, chromium, and sulfur as a minor component, The electrochemical cell has a first region and a second region located downstream of the first region in the fuel gas flow direction through which the fuel gas flows. The content of the minor component in the first volume of the portion of the air electrode that is placed in the first region is: The content of the aforementioned minor component in the second volume of the portion of the air electrode that is located in the second region is greater than the content of the aforementioned minor component in the second volume of the portion located in the second region. Electrochemical cell.

2. In the electrochemical cell according to claim 1, Used as a solid oxide electrolytic cell, Electrochemical cell.

3. In the electrochemical cell according to claim 1 or claim 2, The content of the minor component in the first volume is It is 0.01% by mass or more and 5.0% by mass or less. The content of the aforementioned minor component within the second volume is It is 0.001% by mass or more and 1.5% by mass or less. Electrochemical cell.

4. In the electrochemical cell according to claim 1 or claim 2, The content of the aforementioned auxiliary component is the content within a volume of 10% to 90% of the surface relative to the thickness of the air electrode. Electrochemical cell.

5. In the electrochemical cell according to claim 1 or claim 2, The fuel electrode receives 25 liters / cm³ of the fuel gas. 2 ) 130 liters / (min・cm) 2 ) Used by being supplied at the following flow rates: Electrochemical cell.

6. In the electrochemical cell according to claim 1 or claim 2, The air electrode contains an oxygen-containing gas. 30 liters / (minute / cm²) 2 ) 50 liters / (min / cm) 2 ) Used by being supplied at the following flow rates: Electrochemical cell.

7. In the electrochemical cell according to claim 1 or claim 2, The volume of the air chamber facing the aforementioned air electrode is 9 cm 3 11 cm and above 3 and below Electrochemical cell.

8. In the electrochemical cell according to claim 1 or claim 2, The main component of the air electrode is La x Sr y CoO 3-δ Or La x Sr y CoFeO 3-δ In that case, The ratio of the content of the minor component in the second volume to the content of the minor component in the first volume is: It is between 0.1 and 0.

9. Electrochemical cell.

9. In the electrochemical cell according to claim 1 or claim 2, The main component of the air electrode is Sm x Sr y CoO 3-δ In that case, The ratio of the content of the minor component in the second volume to the content of the minor component in the first volume is: It is between 0.1 and 0.

9. Electrochemical cell.

10. An electrochemical cell according to claim 1 or claim 2, The solid electrolyte layer comprises a separator with an open center, Electrochemical cell with separator.

11. An electrochemical cell stack comprising a plurality of electrochemical cells according to claim 1 or claim 2 stacked on top of each other.

12. The electrochemical cell stack according to claim 11, A vaporizer that generates water vapor supplied to the electrochemical cell stack, A heat exchanger that performs heat exchange with the gas supplied to the electrochemical cell stack, A heater for heating the electrochemical cell stack, An insulating material housing the electrochemical cell stack, the vaporizer, the heat exchanger, and the heater inside, Equipped with, Hot module.

13. A hydrogen production apparatus comprising the hot module described in claim 12.

Citation Information

Patent Citations

  • Electrochemical reaction cell stack

    JP2023080459A